The advertising effectiveness of higher education institutions reviewed from message framing - Euis Soliha; Ajeng Aquinia; Suzy Widyasari; Kristina Anindita Hayuningtias (Jurnal Manajemen dan Pemasaran Jasa, 2022)
This study aimed to investigate the effect of message framing on prospective students' attitudes and the impact on their intention to select a college. Marketers often face difficulties expressing messages positively or negatively. This study was conducted on Vocational and High School students using an experimental laboratory design with positive and negative message framing advertisements. Manipulation checks were conducted on 30 participants to test whether they could differentiate between the two. The results showed a significant difference in belief and evaluation of advertisements using positive and negative message framing, indicating both can be differentiated. Furthermore, hypothesis tests using Smart PLS showed no difference in consumer attitudes in university advertisements using positive and negative message framing, resulting to have the same attitude. The second hypothesis test showed that consumer attitudes positively and significantly affect the prospective students’ intentions.